Hubungan antara Asupan Makronutrien dan Status Nutrisi Dengan Kekuatan Otot Pada Lansia di Panti Werdha Jakarta - halim, Rita halim; Sukmaniah, Sri (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2020)
Background: The decrease of muscle mass and strength in elderly people will affect the functional capacity and increase the risk of sarcopenia. One factor that can affect the loss of muscle mass and strength in elderly is the decrease in nutrition intake i.e macronutrient especially protein and branched chain amino acids (BCAA). The aim of this study is to examine the association between muscle strength intake with macronutrient intake and nutritional status in elderly people. Methods: The methodology of this research is a cross-sectional study with 52 elderly people from April-May 2016. Macronutrient intake is obtained from 2x24 hours food records. Anthropometric measurement is performed by using Seca electrodigital scale and knee height caliper. Blood sampling to measure prealbumin was performed after the subjects fasted for ± 8 hours, and muscle strength was measured with a Jamar’s handgrip dynamometer. Results: The results show significant possitive correlation between handgrip strength with energy intake( r=0,32 dan p=0,02) and carbohydrate intake (r=0,46 dan p=0,01). However, fat intake, protein intake, BCAA intake, serum prealbumin, and BMI have no correlation with handgrip strength. Conclusion: This study concludes that energy intake, especially from carbohydrate intake, can affect muscle strength in elderly. Keywords: macronutrient intake, nutritional status, serum prealbumin, muscle strenght